Nomenclatural notes on the economically important Flaming Katy, Kalanchoe blossfeldiana (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2022)
As part of a review of the names applied to economically important species of Kalanchoe (Crassulaceae subfam. Kalanchooideae), the nomenclature and typification of the name Kalanchoe blossfeldiana are reviewed. The type of this species name is clarified in a second-step lectotypification. The selection of desirable hybrids and cultivars based on K. blossfeldiana, and of hybrids and cultivars of which it is a parent, has developed into a global horticultural industry.